2009
DOI: 10.1143/jjap.48.080203
|View full text |Cite
|
Sign up to set email alerts
|

Marked Enhancement of Optical Kerr Signal in Proportion to Fourth Power of Quality Factor of a GaAs/AlAs Multilayer Cavity

Abstract: The enhanced optical Kerr effect in a GaAs/AlAs multilayer cavity has been studied by numerical simulation using the self-consistent transfer matrix method. The simulated Kerr signal intensity of the cavity mode ( $ 1504 nm) markedly increases with increasing multilayer period because of the high quality factor (Q) of the multilayer cavity. The simulation results reveal that Kerr signal intensity increases in proportion to Q 4 , which is well explained by the enhanced nonlinear phase shift owing to (1) the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…It has been thus reported that the Kerr signal is proportional to Q 4 in the numerical simulation [75].…”
Section: Kerr Nonlinearitymentioning
confidence: 84%
See 1 more Smart Citation
“…It has been thus reported that the Kerr signal is proportional to Q 4 in the numerical simulation [75].…”
Section: Kerr Nonlinearitymentioning
confidence: 84%
“…These two effects can doubly enhance the switching performance in certain configuration as the one we will introduce in the Kerr nonlinearity measurement in Sec.3 [75].…”
Section: Enhancement Of Optical Nonlinearitymentioning
confidence: 97%
“…We also experimentally demonstrated an ultrafast response of the optical Kerr signal of less than one picosecond [8], which was limited by the photon lifetime of the cavity. Furthermore, we recently demonstrated the strong dependence of the optical Kerr signals on the Q-factor of the micro-cavity [9]. These results indicate that the strongly enhanced optical intensity due to the cavity effects plays an important role in the nonlinear optical response of the materials in the structure.…”
mentioning
confidence: 75%
“…We have demonstrated the enhancement of the optical Kerr signal from the cavity with InAs QDs compared with that without QDs. 26) Using improved techniques, we have investigated the FWM in a GaAs=AlAs triple-coupled cavity with 3.4 ML InAs QDs, which were embedded in a strain-relaxed In 0.35 Ga 0.65 As layer to extend the resonance wavelength above 1.5 µm. 27) An equivalent effective optical thickness of three cavity layers was realized using a controlled lateral thickness variation across the wafer.…”
Section: Introductionmentioning
confidence: 99%